Peran Metode Montessori dalam Mengembangkan Kemandirian Anak Usia Dini: Studi Literatur - Puspitaloka, Viny Anggradini; Azizah, Siti Nur; Irbah, Ariq Nurjannah (Institut Agama Islam Ngawi, 2026)
Independence in early childhood is a critical aspect of social-emotional development and decision-making, yet systematic evidence regarding the influence of the Montessori method on child independence across different contexts remains limited. This study aims to synthesize the impact of Montessori through a literature review of national and international research. The analyzed literature includes journal articles from the last five years and relevant books from the last ten years, focusing on guided freedom, practical life activities, and the teacher’s role as a facilitator. The synthesis reveals that the Montessori method consistently supports self-regulation, decision-making, and personal responsibility in children, both locally and internationally. Teachers play a crucial role in providing proportional guidance, allowing children to learn independently while staying on track. The study also identifies gaps in the literature, including the lack of systematic comparative studies between national and international findings and limited integration of empirical results with the theoretical Montessori framework. Consequently, this synthesis strengthens the theoretical concept of auto-education and provides practical guidance for early childhood educators in designing learning environments that foster sustainable child independence.